1998
DOI: 10.1007/bf03012913
|View full text |Cite
|
Sign up to set email alerts
|

Triggering delay time and work of breathing in three paediatric patienttriggered ventilators

Abstract: Purpose: To compare the effectiveness of three patient-triggered ventilators by evaluating triggering delay time and pressure-volume loops during initiation of inspiration. Methods: In a two-part study, a model lung was used in part I and 20 children, after tracheal intubation, in part 2. Triggering delay time and work of breathing 0AIOB) during pressure support ventilation using three patient-triggered ventilators: Servo Ventilator 300 TM VIP Bird", and SLE 2000 Neonatal Ventilator TM. Triggering delay time w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The effect of the delay is that during elastic unloading, no support would be provided for up to 33% of the infant's inspiratory effort assuming this to be 0.3 s in duration 10. It has been demonstrated that the longer the ‘trigger’ delay the greater the increase in the work of breathing,11 which is undesirable as an increased work of breathing can lead to muscle fatigue and has been associated with failed extubation in prematurely born infants 12. In adults, there has been an additional anxiety that a long delay will prolong inspiration into expiration 13.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the delay is that during elastic unloading, no support would be provided for up to 33% of the infant's inspiratory effort assuming this to be 0.3 s in duration 10. It has been demonstrated that the longer the ‘trigger’ delay the greater the increase in the work of breathing,11 which is undesirable as an increased work of breathing can lead to muscle fatigue and has been associated with failed extubation in prematurely born infants 12. In adults, there has been an additional anxiety that a long delay will prolong inspiration into expiration 13.…”
Section: Discussionmentioning
confidence: 99%